2000
DOI: 10.1364/josab.17.001992
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of azobenzene nonlinear optical chromophores: the influence of structure and environment

Abstract: The photodegradation of a variety of donor-acceptor-substituted azobenzene nonlinear optical chromophores has been studied. The variables examined that influence the rate of degradation include chromophore and host polymer structure, irradiation wavelength, temperature, and atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 26 publications
3
67
0
Order By: Relevance
“…It should be pointed out that the change of the refractive index of the hybrid film caused by the real-time heating is totally reversible, that is, the initiate data can be fully recovered after the sample is cooled down and irradiated by the UV irradiation at 514 nm for enough time. Besides the most common employed PMMA matrix, several other polymers have also been used as host matrix to dope DR1 molecules, some of which have higher T g than our TiO 2 /ormosil hybrid material, such as polyethersulfone (PES) and polyimide (Ultem) [11], while others like polyphenylene-vinylene (PPV) [31] and poly (vinyl alcohol) (PVA) [32] have lower T g . These polymers films have their own advantages in the enhancement of photostability, but the unadjustable component makes them difficult have the flexible properties, including rigidity and refractive index, as compared to the asprepared organic-inorganic hybrid films here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that the change of the refractive index of the hybrid film caused by the real-time heating is totally reversible, that is, the initiate data can be fully recovered after the sample is cooled down and irradiated by the UV irradiation at 514 nm for enough time. Besides the most common employed PMMA matrix, several other polymers have also been used as host matrix to dope DR1 molecules, some of which have higher T g than our TiO 2 /ormosil hybrid material, such as polyethersulfone (PES) and polyimide (Ultem) [11], while others like polyphenylene-vinylene (PPV) [31] and poly (vinyl alcohol) (PVA) [32] have lower T g . These polymers films have their own advantages in the enhancement of photostability, but the unadjustable component makes them difficult have the flexible properties, including rigidity and refractive index, as compared to the asprepared organic-inorganic hybrid films here.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Xie et al [5], in solid state doped materials, their efficiency and stability strongly depend on the properties of the matrix, such as the glass transition temperature (T g ) and the structural properties of the matrix. The polymer, such as PMMA and PPV, was widely used as a matrix material [6][7][8], but the low stability under UV irradiation limits its application [9], hence, during the last two decades, many research works on the stability of the azo-doped materials have been reported [10,11]. For examples, the polymers with high T g and derived by new synthetic method were employed to achieve a more stable material system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the point dipole approximation, an analytical expression is readily obtained for the order parameter relating molecular first hyperpolarizability β to macroscopic electro-optic activity, r 33 . While this result is useful for understanding the attenuation of electro-optic activity observed for prolate ellipsoid-shaped chromophores incorporated into commercial polymers to form composite materials, the lower right equation of Fig.…”
Section: I-mentioning
confidence: 99%
“…[19][20][21][22][23] The major issues causing concerns regarding the utilization of organic electro-optic materials relate to thermal and photochemical stability. [24][25][26][27][28][29][30][31][32][33][34][35] Substantial progress have been made in improving and characterizing thermal and photochemical stability including by improved lattice hardening methodologies. Recent results suggest that Telcordia standards can be satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…Since the photoisomerization process is reversible and sensitive to the light polarization, azo-dyes have been used for the fabrication of a broad class of photosensitive materials with varied applications including waveguiding [5], optical switching [6] and optical information storage and processing [7,8]. However, irreversible photoinduced bleaching (photobleaching) can be suffered by the azo-dye molecules [9,10]. If this occurs, it means that the molecule loses absorption intensity and thus the activity of the chromophore is lost.…”
Section: Introductionmentioning
confidence: 99%